Homesickness as Seen in Harry Potter’s Character in J. K. Rowling’s Harry Potter and the Prisoner of Azkaban - Januar Ramadhan; Rahmawan Jatmiko (Lexicon, 2019)
This research attempts to examine the effects of homesickness on Harry potter in J. K. Rowling’s Harry Potter and the Prisoner of Azkaban. Homesickness as a mental illness is prevalent in people; therefore, the investigation used Harry Potter as its subject. The research adopts the theory of homesickness proposed by Fisher (1989). The research shows the harshness of being homesick in a society that we have little control of and in situations where we have no choice on how to proceed. It highlights the need of attachments in a social sense for individuals who are suffering from homesickness because it is one of the definite cure for a serious and dangerous mental illness. It can affect anyone regardless of age, living conditions, and state of mind.